KARTU TANDA PENDUDUK TANPA KOLOM AGAMA DALAM PERSPEKTIF EKSISTENSIALISME SARTRE - Surya Desismansyah Eka Putra (Universitas Negeri Malang, 2016)
The concept of freedom is a form of analysis on how the free word was present and exist as a tangible manifestation of the contemporary world in the face of uncertainty. Humans really want to look for its existence as a creature. Existentialism tried to leave the path of light that human nature is the existence in the world. Is a self-proclaimed Sartre the existentialist philosophy of abiding by its main slogan,